(untitled) (Research, Society and Development, 2022)
Measles is an infectious viral disease characterized by fever, dry cough, maculopapular rash and Koplik´s spots. Its control is obtained mainly through the Triple Viral vaccine, however, in 2016, Brazil again showed an increase in cases, causing the loss of the measles eradication certificate. Thus, the present study aimed to survey the incidence, in addition to describing important aspects, characterization, and verification of the epidemiological situation of measles in Brazil. For this, a cross-sectional population-based study was carried out, using secondary data in which an epidemiological survey of Measles cases reported in Brazil, in 2020 up to the 32nd epidemiological week. During the study period, 15,335 suspected measles cases. The state with the highest incidence of measles was Pará (91.15). The age group with the highest incidence was younger than 1 year old (104), while the highest number of cases was recorded in the age group between 20 and 29 years old (n=2,407), with no significant difference between the sexes. The cases evolved to a cure, but in the 32nd epidemiological week of 2020, 5 deaths were recorded in the states of Pará (n=3), São Paulo (n=1), and Rio de Janeiro (n=1). The states of Pará and São Paulo had a percentage of positive IgM tests of 50.8 and 37%, and only 3.2% (n=28) of cases were inconclusive, especially in other unlisted states, Rio de Janeiro, Santa Catarina, and São Paulo. In this way, the present study provides relevant information on the epidemiological situation in Brazil.